COMMUNICATION ACCOMMODATION THROUGH TIKTOK ACCOUNT @MEGAMUSTIKASUNDARI2 - Rifaldi, Muhammad; Sinduwiatmo, Kukuh (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze how the TikTok account @megamustikasundari2 establishes personal communication with its audience through an authentic and empathetic communication approach. Method: Employing a descriptive qualitative method with the Communication Accommodation Theory as the analytical framework, the research explores strategies of convergence, divergence, and over-accommodation applied in the creator’s interactions. Results: The findings indicate that the account owner effectively fosters emotional closeness by utilizing familiar language, a consistent communication style, and active engagement through personalized greetings, comment responses, and content adaptation to follower characteristics. Furthermore, non-verbal elements such as facial expressions, tone of voice, and gestures significantly enhance the perceived empathy and authenticity of communication. Novelty: This study contributes to the understanding of how social media creators can apply accommodation strategies to build genuine and loyal digital communities, emphasizing TikTok as an emerging platform for relational communication and digital identity construction in contemporary interpersonal communication studies.